The First Effect of COVID-19 Pandemic on Starting Biological Disease Modifying Anti-Rheumatic Drugs: Outcomes from the TReasure Real-Life Database - Kanitez, Nilufer Alpay; Kiraz, Sedat; Dalkilic, Ediz; Kimyon, Gezmis; Mercan, Ridvan; Karadag, Omer; Kalyoncu, Umut (Aves, 2022)
Objective: The coronavirus disease 2019 pandemic has been resulting in increased hospital occupancy rates. Rheumatic patients cannot still reach to hospitals, or they hesitate about going to a hospital even they are able to reach. We aimed to show the effect of the first wave of coronavirus disease 2019 pandemic on the treatment of biological disease-modifying anti-rheumatic drugs in patients with rheumatoid arthritis or spondyloarthritis. Methods: Patients were divided into three groups as follows: pre-pandemic (Pre-p: starting on biological disease-modifying anti-rheumatic drug therapy for the first time within 6 months before March 11, 2020); post-pandemic A (Post-p A: starting on biological disease-modifying anti-rheumatic drug therapy for the first time within the first 6 months after March 11, 2020); post-pandemic B (Post-p B: starting on biological disease-modifying anti-rheumatic drug therapy for the first time within the second 6 months). Results: The number of rheumatoid arthritis patients in the Post-p A and B groups decreased by 51% and 48%, respectively, as compared to the Pre-p group similar rates of reduction were also determined in the number of spondyloarthritis patients. The rates of tofacitinib and abatacept use increased in rheumatoid arthritis patients in Post-p period. Conclusion: The number of rheumatoid arthritis and spondyloarthritis patients starting on biological disease-modifying anti-rheumatic drugs for the first time decreased during the first year of the coronavirus disease 2019 pandemic.
Keywords: Biological disease-modifying anti-rheumatic drug; coronavirus disease 2019; rheumatoid arthritis; spondyloarthritis